Heresies heresy and orthodoxy in the history of the church - Brown, Harold O.J. 1933- (Peabody, MA Hendrickson, 1988)
Includes bibliographical references and index.
Keywords: Theology, doctrinal -- history; Jesus Christ -- history of doctrines; Heresies, Christian -- history